INVESTIGATING THE MOST COMMON STRATEGY IN TRANSLATING ENGLISH IDIOM MADE BY ENGLISH DEPARTMENT STUDENTS - Aruji, Fitra Maisya (RETAIN, 2021)
Idiomatic translation becomes one of the skill that English Department students should master. However, some students find it difficult to translate it since idiom cannot be translated literally. Therefore, the students need certain strategy to overcome the difficulties. Baker (2018) proposed four strategies such as using similar meaning and form, using similar meaning but dissimilar form, translation by paraphrase, and translation by omission. The aims of this study are to find out which strategy that most of the students use and the reason why they choose it. The researcher got the answer for the first research question from the students’ works and questionnaire. After knowing which strategy that is considered as the most common strategy, the researcher analyzes the students’ works then interviews the students who choose it to get the answer for the second research question. The result shows that translation by paraphrase becomes the most common strategy. The reasons why they choose it are various. The common reason is this strategy is easier compared to the other strategies. Keywords: idiomatic translation, strategy, English Department students.